Balneotherapy for the treatment of post-COVID syndrome: a randomized controlled trial - Diana Ovejero; Anna Ribes; Judit Villar-García; Marta Trenchs-Rodriguez; Daniel Lopez; Xavier Nogués; Robert Güerri-Fernandez; Natalia Garcia-Giralt (BMC Complementary Medicine and Therapies)
Abstract Background Post-Acute COVID Syndrome (PACS) is a complex disorder that currently lacks effective evidenced-based therapies to manage it. This randomized controlled trial aims to evaluate the effects of balneotherapy (BT) on PACS symptomatology. Methods Ninety-eight adults with PACS visited at Hospital del Mar Research Institute, Barcelona (Spain) were included to the study. Participants in the intervention group (n = 51) were allocated to 12 sessions of BT and aquatic exercises delivered in one month while the control group (n = 47) did not. The primary outcome was to evaluate the absolute change in questionnaire scores between baseline and two follow-up points: immediately after balneotherapy (or one-month post-baseline for the control group) and 2 months post-baseline. The following scales/questionnaires were employed: Post-COVID-19 functional status scale, mMRC dyspnea Scale, SF-36, Pittsburgh Sleep Quality Index (PSQI), Hospital Anxiety and Depression Scale (HADS), Memory failures in everyday life following severe head injury, and Visual Analogic Scale (VAS). Results Forty-seven patients in the BT group and 43 in the control group completed the study. The majority of participants were middle-aged women (> 84%; mean age 48 years), and the most prevalent symptoms were fatigue, musculoskeletal pain, and neurocognitive impairment (> 88%). Noteworthy, the vast majority did not undergo a severe primary infection (ICU admissions < 3%). After BT, significant improvement was detected in the BT group vs. the control group in various SF-36 domains, PSQI total score (Beta-coefficient [95%CI] 2.641 [1.15;4.12]; p -value = 0.003), HAD’s anxiety subscale (Beta-coefficient [95%CI] 1.72 [0.40;3.03;p-value = 0.023), and VAS (Beta-coefficient [95%CI] 1.625 [0.32;2.96]; p-value = 0.026). Among these, SF-36’s energy/fatigue and pain subscales exhibited the most prominent changes with a Beta-coefficient [95%CI] of -17.45 [-24.23;-10.66] and − 21.634 [-30.48;-12.78], respectively (p-value < 0.0001). No severe adverse effects were reported during BT although seventeen patients reported mild and transient worsening of preexisting symptoms, particularly fatigue/post-exertional malaise mainly in the first sessions of BT. Conclusion Balneotherapy comprise an effective therapeutic modality that can alleviate several symptoms that characterize PACS, particularly musculoskeletal pain and fatigue. However, the sustainability of these effects over time remains uncertain, as evidenced by the loss of some between-group differences at the one-month follow-up. Trial registration ClinicalTrials.gov NCT05765591 (13/03/2023).